2008
DOI: 10.1111/j.1440-1754.2008.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease with lymphadenopathy and fever as sole initial manifestations

Abstract: Although a delay in diagnosis and stronger inflammation were found in LKD patients, such differences did not have any significant effect on patients' outcomes as assessed by the frequency of IVIG administration and the presence of CALs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 17 publications
2
27
2
3
Order By: Relevance
“…1, 9, 10 A Japanese comparison of 14 patients with NFKD and 24 patients with BCL 12 revealed that patients with NFKD, as in our study, were older and had higher CRP levels. In contrast, their patients with NFKD had higher WBC, ANC, and aspartate aminotransferase levels and lacked the relative anemia and thrombocytopenia which we observed.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…1, 9, 10 A Japanese comparison of 14 patients with NFKD and 24 patients with BCL 12 revealed that patients with NFKD, as in our study, were older and had higher CRP levels. In contrast, their patients with NFKD had higher WBC, ANC, and aspartate aminotransferase levels and lacked the relative anemia and thrombocytopenia which we observed.…”
Section: Discussionsupporting
confidence: 61%
“…Compared with those with typical KD, previously reported patients with NFKD 9, 10 and patients with KD with cervical adenopathy 3, 4 were older and ill longer prior to diagnosis and had higher CRP 9, 10 and ESR values. 3 In the largest previous series (16 patients with NFKD and 171 with typical KD), patients with NFKD more often required repeated administration of IVIG and had an increased risk of coronary artery lesions.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Patients with Kd with cervical lymphadenopathy as their dominant initial presentation were shown to be older and diagnosed later than other patients. 13,14 two other case series also reported that, in these patients, diagnosis was made on an average of 8.2 days of illness. 20,21 Comparatively delayed diagnosis in such patients highlights difficulty in timely diagnosis.…”
Section: Discussionmentioning
confidence: 89%
“…Patients with Kd presenting with only fever and cervical lymphadenopathy are reported to be older than patients with other presentations. 13,14 incomplete Kd, by contrast, is more common in infants. 2,15 understanding these differences in clinical manifestation is particularly helpful to provide timely identification of patients with Kd.…”
mentioning
confidence: 81%